Development of the Model and Digital Business Insight for Primary and Secondary School Teachers in Indonesia-Thailand - Indrayani, Syarthini; Arman, Andi; Marhumi, Siti; Nurinaya, Nurinaya (Technium Sustainability, 2023)
Digital business is a business model that uses digital technology. All people can become successful entrepreneurs in this digital era, both home-based people, practitioners, and even academics can plunge into this world. With this, business competition requires that its human resources (HR) must not stutter in incorporating technological elements into the business they run. The main problem of Eakapapsasnawich Islamic School Thailand School Teachers lies in the lack of insight related to digital business models that must be run and digital business insights, the absence of a forum that focuses on digital business development and the absence of activities related to the development of digital business models and insights that are present to educate Eakapapsasnawich Islamic School Thailand, inspiring the PKM Team to educate Eakapapsasnawich Islamic School Teachers Thailand related to understanding digital business insights and introducing several digital business models that can support the improvement of the business it is engaged in. The method used is the provision of material through lectures, motivation, discussion, and practice. The output target of this program is scientific articles published through service journals indexed by Sinta, and increasing teacher empowerment in running a business using a digital-based business model.